1991
DOI: 10.1063/1.350286
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of space-charge effects in lead zirconate-titanate memories

Abstract: By combining Auger data on the width of an oxygen depletion layer near the Pt electrodes with a modified Langmuir–Child law for the leakage current: I(V) = aV + bV2, we deduce parameters related to the space-charge density and field in 210-nm-thick PbZr1−xTixO3 memories. The results are compared with the space charge fields inferred by Okazaki (∼10 kV/cm for PZT), which involve measuring the switching speeds ts(E) for positive and negative voltages. Differences in the voltage dependencies of the leakage curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
140
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(145 citation statements)
references
References 15 publications
5
140
0
Order By: Relevance
“…From this study, it can be demonstrated that the microstructures of ferroelectric films play an important role in their conductivity properties. 12 Comparing with literature data, our films present a higher leakage current than the films obtained on highly oriented LaNiO 3 -buffered Pt/ Ti/ SiO 2 / Si substrates by sol-gel process. 13 Since the conductivity is strongly affected by the characteristics of the film-electrode interface, the lower leakage current observed in the literature may be attributed probably to differences in grain size, density, and preferred orientation due to differences in the metalferroelectric-metal configuration.…”
supporting
confidence: 38%
“…From this study, it can be demonstrated that the microstructures of ferroelectric films play an important role in their conductivity properties. 12 Comparing with literature data, our films present a higher leakage current than the films obtained on highly oriented LaNiO 3 -buffered Pt/ Ti/ SiO 2 / Si substrates by sol-gel process. 13 Since the conductivity is strongly affected by the characteristics of the film-electrode interface, the lower leakage current observed in the literature may be attributed probably to differences in grain size, density, and preferred orientation due to differences in the metalferroelectric-metal configuration.…”
supporting
confidence: 38%
“…As a result, the density of oxygen vacancies, which are apparently present in this perovskite layer 52,53 despite our attempts to suppress their formation here during the fabrication process (see Methods), is expected to be the same in both studied FTJs. Hence, the observed giant electrode effect on TER cannot be attributed to the motion of oxygen vacancies across the junction as well.…”
Section: Discussionmentioning
confidence: 99%
“…From this study, it can be demonstrated that the microstructures of ferroelectric films play an important role in their conductivity properties. 12 Further, different regimes can be distinguished in the I-V characteristics ͑Fig 7͒. At very low electric fields, the films display nearly ohmic conduction.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that J-E characteristics of the LSCO annealed film can be fitted well with polynomials suggests that the role of traps is not significant for this film. 12 As a consequence, a model based on SCL emission provides the most consistent explanation of the J-E characteristics of the BLT film on LSCO bottom electrode. The formation of space charge can be attributed to the platelike nature of the film, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%